Everolimus for patients with metastatic renal cell carcinoma refractory to anti-VEGF therapy: Results of a pooled analysis of non-interventional studies. Issue 16 (November 2015) - Albiges, Laurence; Kube, Ulrich; Eymard, Jean-Christophe; Schmidinger, Manuela; Bamias, Aristotelis; Kelkouli, Nadia; Mraz, Bernhard; Florini, Styliani; Guderian, Gernot; Cattaneo, Agnese; Bergmann, Lothar
Abstract Aim To assess the efficacy and safety of everolimus in patients with metastatic renal cell carcinoma (mRCC) who failed one or two anti-VEGF therapies. Patients and methods Data from four prospective, non-interventional studies conducted in Germany, France, Greece and Austria were pooled for this analysis. Patients with mRCC of any histology (clear cell or non-clear cell) were included. VEGF-refractory patients received everolimus 10 mg/day until disease progression or unacceptable toxicity. The primary objective was to determine everolimus efficacy as measured by time to progression (TTP; from baseline to progression). Results The overall population comprised 632 patients; 493 patients received everolimus in the second-line setting. Most patients were of favourable/intermediate MSKCC risk (91%), had clear cell mRCC (89%), and had undergone nephrectomy (89%). Median TTP was 6.3 months (95% confidence interval [CI], 5.9–6.8) for the overall population and 6.4 months (95% CI, 5.8–6.9) for the second-line everolimus population. Similarly, median progression-free survival was 5.5 months (95% CI, 5.0–6.1) for the overall population and 5.8 months (95% CI, 5.0–6.4) for second-line everolimus population. Best tumour response (n = 349) was complete or partial remission in 12% of patients and stable disease in 59% of patients. Overall population median overall survival (OS) was 11.2 months (95% CI, 9.0–not reached). Commonly reported adverse events (AEs) (any grade) were stomatitis (25%), anaemia (15%) and asthenia (11%). Conclusions Results of this pooled analysis provide evidence of safety and effectiveness of second-line everolimus in routine clinical use and support everolimus as a standard of care for VEGF-refractory patients with mRCC.